Anti-biofilm and antimicrobial effects of zerumbone against Bacteroides fragilis. (June 2019) - Kim, Hye-Rim; Rhee, Ki-Jong; Eom, Yong-Bin
Abstract: Enterotoxigenic Bacteroides fragilis (ETBF) can form biofilms in the colon mucosal membrane and may promote chronic infection and tumor formation. The objective of this study was to determine the effect of zerumbone extracted from Zingiber zerumbet (L.) Smith, on B. fragilis biofilm formation. Inhibitory effects of zerumbone on planktonic cell growth and biofilm formation were examined by crystal-violet biofilm assays and XTT metabolic assays. Results showed that zerumbone significantly inhibited biofilm formation and eradicated established biofilms. Furthermore, B. fragilis biofilms inhibited by zerumbone were observed by confocal laser scanning microscopy. qRT-PCR was used to support the phenotypic results and to investigate the expression levels of an efflux pump-related gene ( bmeB ). Specifically, among the efflux pump-related genes, zerumbone significantly suppressed the expression level of bmeB12 . These results indicate that zerumbone might be a promising candidate as an anti-biofilm and antimicrobial agent to treat and prevent biofilm-related infections caused by B. fragilis .